Mechanisms linking plant community properties to soil aggregate stability in an experimental grassland plant diversity gradient - G. Pérès; D. Cluzeau; S. Menasseri; J. F. Soussana; H. Bessler; C. Engels; M. Habekost; G. Gleixner; A. Weigelt; W. W. Weisser; S. Scheu; N. Eisenhauer (Plant and Soil, 2013)

A multi-proxy approach to reconstruct hydrological changes and Holocene climate development of Nam Co, Central Tibet - I. Mügler; G. Gleixner; F. Günther; R. Mäusbacher; G. Daut; B. Schütt; J. Berking; A. Schwalb; L. Schwark; B. Xu; T. Yao; L. Zhu; et al. (Journal of Paleolimnology, 2010)

Plant diversity effects on soil microorganisms support the singular hypothesis - N. Eisenhauer; H. Beßler; C. Engels; G. Gleixner; M. Habekost; A. Milcu; S. Partsch; A. C. W. Sabais; C. Scherber; S. Steinbeiss; A. Weigelt; W. W. Weisser; et al. (Ecology, 2010)
The global decline in biodiversity has generated concern over the consequences for ecosystem functioning and services. Although ecosystem functions driven by soil microorganisms such as plant productivity, decomposition, and nutrient cycling are of particular importance, interrelationships between plant diversity and soil microorganisms are poorly understood. We analyzed the response of soil microorganisms to variations in plant species richness (1–60) and plant functional group richness (1–4) in an experimental grassland system over a period of six years. Major abiotic and biotic factors were considered for exploring the mechanisms responsible for diversity effects. Further, microbial growth characteristics were assessed following the addition of macronutrients. Effects of plant diversity on soil microorganisms were most pronounced in the most diverse plant communities though differences only became established after a time lag of four years. Differences in microbial growth characteristics indicate successional changes from a disturbed (zymogeneous) to an established (autochthonous) microbial community four years after establishment of the experiment. Supporting the singular hypothesis for plant diversity, the results suggest that plant species are unique, each contributing to the functioning of the belowground system. The results reinforce the need for long‐term biodiversity experiments to fully appreciate consequences of current biodiversity loss for ecosystem functioning.

Isotopic evidences for microbiologically mediated and direct C input to soil compounds from three different leaf litters during their decomposition - M. Rubino; C. Lubritto; A. D’Onofrio; F. Terrasi; C. Kramer; G. Gleixner; M. F. Cotrufo (Environmental Chemistry Letters, 2009)

Oxygen isotope ratios of sedimentary biogenic silica reflect the European transcontinental climate gradient - J. J. Tyler; M. J. Leng; H. J. Sloane; D. Sachse; G. Gleixner (Journal of Quaternary Science, 2008)
Oxygen isotope ratios of biogenic silica offer considerable potential in tracing past climate change using both marine and lacustrine sediment records. Despite recent improvements and standardisation in preparatory and analytical methods, evidence for a systematic relationship between climate parameters and the oxygen isotope composition of sedimentary diatom silica ( δ 18 O silica ) is contradictory. In particular, observed differences between the δ 18 O silica of living and sedimentary diatom silica in both lake and marine environments question the validity of applying isotope fractionation models derived from living diatoms to reconstructing climate from sediment records. In order to address this issue, oxygen isotope ratios of biogenic silica ( δ 18 O silica ) are examined from a suite of lake surface sediment samples which span a large climatic gradient across western Europe. δ 18 O silica values are strongly correlated with air temperature and the isotope composition of precipitation ( δ 18 O P ). When evaporation of lake waters is accounted for, the time‐averaged surface sediment data suggest a fractionation of ∼35‰ between water and biogenic silica. However, the effect of temperature appears less marked than that observed between contemporary diatoms and lake water over short timescales, suggesting that diagenetic processes may lead to a reduction in the temperature sensitivity of sediment δ 18 O silica records. Comparison of δ 18 O silica data with δ D analysed from n ‐alkanes of aquatic origin ( n ‐C17, n ‐C21 and n ‐C23) demonstrates that the slope of the regional δ 18 O: δ D water line is preserved within the sediment record, offering exciting potential for palaeoclimate research. © Natural Environment Research Council (NERC) copyright 2008. Reproduced with the permission of NERC. Published by John Wiley & Sons, Ltd.

An isotopic method for testing the influence of leaf litter quality on carbon fluxes during decomposition - Mauro Rubino; C. Lubritto; A. D’Onofrio; F. Terrasi; G. Gleixner; M. F. Cotrufo (Oecologia, 2007)